IMPLEMENTATION OF THE 5E LEARNING CYCLE MODEL THROUGH MAGIC CARD LEARNING MEDIA ON CRITICAL THINKING SKILLS - Nanik Rujiyah Masruroh; Siska Ayu Wulandari; Agus Santoso (Jurnal Pembelajaran Sains, 2023)
This study aims to determine: (1) the implementation of learning using the 5E learning cycle model through magic card learning media, (2) the development of critical thinking skills, and (3) student responses after receiving the lessons. This research uses a pre-experimental design. The study was conducted with 8th-grade students at Sugio 2 Middle School. The research design was a one-group pre-test post-test design. The sample consisted of 64 8th-grade students selected through purposive sampling. To measure critical thinking skills, a critical thinking ability test with 10 essay questions was used. The observation results yielded an average value of 3.95 using the Ricketts scale. Student responses showed an average percentage of 92.24. Data analysis was performed using the N-gain test with a score of 0.292. Based on the results of applying the 5E learning cycle model through magic card learning media, students' thinking skills are categorized as effective.